1973
DOI: 10.6028/nbs.ir.73-184
|View full text |Cite
|
Sign up to set email alerts
|

A cell model for isoperibol calorimeters

Abstract: A Calorimeter can be modeled as a large number of volume elements or cells in each of which the temperature may be considered uniform, and each of which can store heat and exchange heat with other cells. Application of the first law of thermodynamics to this set of cells leads to representations of the usual calorimetric equations for the energy change expressed in terms of measurable or estimatable heat capacities, heat transfer coefficients, temperatures, and work terms for the individual cells. Analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…It is always hoped that these compromises do not effect the accuracy of the measurements. Design criteria and possible sources of systematic errors in calorimeters have recently been discussed a priori in a series of papers by West, Churney, and Armstrong [1][2][3][4].1 They also suggest experimental tests to determine whether some systematic errors are likely to occur during calorimetric measurements. Recent work [5] indicated disagreement in results obtained by three calorimeters believed to be capable of measurements of highest accuracy and experimental imprecision of 0_1 percent or less.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is always hoped that these compromises do not effect the accuracy of the measurements. Design criteria and possible sources of systematic errors in calorimeters have recently been discussed a priori in a series of papers by West, Churney, and Armstrong [1][2][3][4].1 They also suggest experimental tests to determine whether some systematic errors are likely to occur during calorimetric measurements. Recent work [5] indicated disagreement in results obtained by three calorimeters believed to be capable of measurements of highest accuracy and experimental imprecision of 0_1 percent or less.…”
Section: Introductionmentioning
confidence: 99%
“…The results in table 6 indicate errors in heat leak corrections in this isoperibol ca lorimeter due to (1) inadequate stirring in the endothermic reaction (-0.5%) and in the exothermic reaction (+ 0.1 %), (2) failure to have I:!..T of the same sign in the calibrations and in the reaction period (+0.3% or more because of erratic results), and (3) failure to measure the energy equivalents and the reaction over the same temperature range (-0.1 %). Erratic results were also obtained for the exothermic TRIS reaction in both the isoperibol and the adiabatic calorimeters when Hel solutions which had been stored for long periods in polyethylene bottles were used.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The design basis for closed isoperibol calorimeters (i.e .. those for which no reactants or products flow across the calorimeter boundary) has been reviewed elsewhere [13). From a review of some previous work on calorimeter theory [15] and on the design practice and data analysis of flow calorimetry [16J, we concluded that the design basis of open calorimeters (i.e., those for which reactants or products do flow across the calorimeter boundary) are essentially the same as those for closed calorimeters. In particular, to account for the enthalpy of the gases entering or leaving the calorimeter proper, the gas flow tubes should be in good thermal contact with the calorimeter water and jacket water, and the measurement junctions of the thermocouples used to monitor the temperatures of the fluids entering and leaving the calorimeter should be located at the interspace.…”
Section: Design Basismentioning
confidence: 99%
“…The corresponding electrical diagram for this analysis is given in figure C-2 In effect, we automatically assume there is no calorimetric error due to non-equivalent sources (i.e. see [181]). …”
Section: ++mentioning
confidence: 99%